The effect of inositol supplementation on blood pressure: A systematic review and meta-analysis of randomized-controlled trials. (August 2021) - Hashemi Tari, Sogol; Sohouli, Mohammad Hassan; Lari, Abolfazl; Fatahi, Somaye; Rahideh, Seyedeh Tayebeh
Summary: Background & aims: Potential effects of inositol supplementation on blood pressure (BP) have been examined in several interventional studies. Nevertheless, findings in this context are controversial. Therefore, the current systematic review and meta-analysis aimed to comprehensively assess the impact of inositol supplementation on BP. Methods: Five online databases including Web of Science, Scopus, Embase, Cochrane, Google Scholar, and PubMed were systematically searched from inception to March 2020. We included all randomized clinical trials (RCTs) evaluating the effects of inositol supplementation on systolic blood pressure (SBP) and/or diastolic blood pressure (DBP) in humans. Results: The random-effects meta-analysis of 7 eligible RCTs demonstrated the significant decline in both SBP (WMD − 5.69 mmHg; 95% CI − 7.35 to − 4.02, P < 0.001) and DBP (WMD − 7.12 mmHg; 95% CI − 10.18 to − 4.05, P < 0.001) following supplementation with inositol. Subgroup analysis showed that studies performed in individuals with metabolic syndrome with a longer duration (>8 weeks) and a dose of 4000 mg resulted in a more effective reduction in SBP and DBP with acceptable homogeneity. Conclusions: The current meta-analysis, indicated that supplementation with inositol significantly decrease SBP and DBP. Further large-scale RCTs with better design are needed to confirm these findings.